Isolation and expression analysis of CsWRKY6, CsWRKY31 and CsWRKY48 genes in tea plant - WANG Pengjie; YUE Chuan; CHEN Di; ZHENG Yucheng; ZHENG Zhilin; LIN Yi; YANG Jiangfan; YE Naixing (浙江大学学报. 农业与生命科学版)
Three WRKY genes were cloned by using reverse transcription-polymerase chain reaction (RT-PCR) technique from the tea plant of ‘Tieguanyin’ cultivar and named as CsWRKY6, CsWRKY31, CsWRKY48 with the GenBank accession numbers of MG298953, MG298958 and MG298961, respectively. Their open reading frames (ORFs) were 1 734, 1 299 and 960 bp long, encoding 577, 432 and 319 amino acids, respectively. Phylogenetic tree and protein domain analysis indicated that all of them belong to class Ⅱ WRKY protein, and contained highly conserved DNA-binding domain of WRKYGQK and zinc finger structures. CsWRKY6 and CsWRKY31 shared the same zinc finger structure model of C-X5-C-X23-H-X-H, whereas CsWRKY48 belonged to C-X4-C-X23-H-X-H. The three genes were expressed in different tissues and had obvious tissue specificity in tea plant. The expression level of CsWRKY6 in old leaves was significantly higher than that in other tissues, while the expression level of CsWRKY31 was the highest in flowers and CsWRKY48 had higher expression level in roots and stems than that in leaves, flowers and fruits. Protein interaction prediction indicated that the three genes were involved in the stress response by interacting with multiple genes. Fluorescence quantitative analysis showed that low temperature treatment could significantly up-regulate their transcript abundance in tea plant leaves. Under drought stress, both CsWRKY31 and CsWRKY48 were induced to the maximum after 12 h. The expression level of CsWRKY48 was dramatically up-regulated after exogenous abscisic acid (ABA) treatment, whereas the expression level of CsWRKY6 and CsWRKY31 was repressed. It is revealed that the three genes are closely related to the resistance in tea plants.